Implementation of Blockchain Technology in Construction Project Management: A Contemporary Approach - Xie Guilin; Kailie Maharjan; Elladdadi Mark (Yayasan Adra Karima Hubbi, 2024)
The construction industry is a sector known for its complexity in terms of project management. The involvement of various parties, the large flow of information, and the challenge of maintaining data validity are major challenges. In an effort to improve efficiency and transparency, blockchain technology is emerging as a potential solution. However, the applicability of this technology in the context of construction project management still requires further research. Research Objectives: This study aims to investigate the possibility and potential application of blockchain technology in construction project management. The main focus is to understand how this technology can improve efficiency, transparency, and data reliability in various aspects of construction project management. Research Methods: This research utilized a qualitative approach with descriptive analysis. Data was collected through a review of related literature as well as case studies of blockchain technology implementation in construction project management in several large-scale projects. An in-depth analysis was conducted to understand the challenges, benefits, and key factors affecting successful implementation. Research Results: The results show that blockchain technology has great potential in improving efficiency and transparency in construction project management. By utilizing features such as distributed ledgers, smart contracts, and secure transaction confirmation, the project management process can become more structured, efficient, and trustworthy. Research Conclusion: In the context of construction project management, the implementation of blockchain technology offers an attractive solution to address existing challenges. Although there are still some technical and policy hurdles that need to be overcome, the long-term potential of this technology in improving the productivity and quality of construction projects is promising. Therefore, strategic steps need to be taken to encourage wider adoption of this technology in the construction industry.